TINDAK TUTUR DIREKTIF PADA RUBRIK LAPORAN MANG SRIPO: SUARA PEMBACA SURAT KABAR SRIWIJAYA POST - Ayu Puspita Indah Sari; Ilham Septiansyah (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2021)
This study aims to find out the forms of directive speech acts that exist in the reader's voice in the Mang Sripo Report rubric of the Sriwijaya Post newspaper. Data analysis was carried out in research since the data collection process. From the results of the analysis, it was found that the form of directive speech acts contained in the Mang Sripo Report Rubric: the voices of readers of the Sriwijaya Post newspaper which the author found had twelve data consisting of the form of asking for seven utterances; ask as many as four utterances, and prohibit as many as one utterances; Of the three forms that have been found, the form that is most commonly found in the form of asking.